Mapping global epidemiology of thyroid nodules among general population: A systematic review and meta-analysis - Mu, Chunyang; Ming, Xin; Tian, Ye; Liu, Yang; Yao, Menglin; Ni, Yinyun; Liu, Yong; Li, Zhihui (Frontiers in Oncology, 2022)
Introduction An emerging public health issue is brought on by the worldwide increase of thyroid nodules (TNs). The goal of the current study is to determine the global prevalence of TNs among the general population. Methods We screened articles published from January 2000 to May 2022. TNs prevalence was calculated with the DerSimonian-Laird random effects model with arcsine transformation. Results 20358 entries were found in our research, and 102 of them met our inclusion criteria. A total of 9276178 individuals have been diagnosed as TN, the overall prevalence was 24.83% (95% CI 21.44-28.55) regardless of the diagnostic techniques. TNs has become more prevalent during the year 2012-2022 (29.29%) compared to year 2000-2011 (21.53%, p=0.02). Besides, we discovered that females (36.51%) were more likely to have TNs than males (23.47%, p<0.01). Interestingly, we found that obesity was correlated with prevalence of TNs. Additionally, age-specific stratified TNs prevalence was found in our results. Discussion This meta-analysis shows that, regardless of country development and economic status, TNs are spreading more widely over the world. Our findings showed a strong correlation between rising TNs prevalence and older age, female sex and elevated weight. To stop the TNs epidemic from spreading over the world, increased awareness, the understanding of the disease and quick action are required.